IMPLEMENTATION OF PROVISION OF LEGAL ASSISTANCE FOR SUSPECTS AT YOGYAKARTA POLICE - Rini Agustine (Fox Justi : Jurnal Ilmu Hukum, 2021)
This study aims to describe (1) the implementation of providing legal aid for suspects at the Yogyakarta Police, (2) the obstacles encountered in the implementation of the provision of legal aid, and (3) efforts to overcome obstacles in the implementation of providing legal aid for suspect at the Yogyakarta Police. This research is a descriptive study with a qualitative research method approach. Research subjects were determined by purposive technique. The research subjects are the Deputy for Criminal Investigation, Police Investigator, Head of Investigative Unit I, Head of Operational Development Affairs and legal advisors as legal aid providers. Data were collected by interview and documentation methods. The results of this study indicate that the implementation of providing legal assistance for suspects who are poor and threatened with imprisonment for five years or more is when the Police, especially the investigators carry out their obligations as regulated in the Criminal Procedure Code, in particular Articles 54 and 56. the suspect at the Yogyakarta Police, namely the limited funds for the implementation of the provision of Legal Aid at the Yogyakarta Police, namely Rp. 3,000,000.00 per case when it should be Rp. 5,000,000.00 per case, the availability of Legal Aid Providers at Poresta Yogyakarta is not yet sufficient, there are some investigators who do not understand about the provision of legal aid for indigent (poor) suspects. Efforts in overcoming obstacles in the implementation of providing legal assistance for suspects at the Yogyakarta Police, namely,